2012
DOI: 10.1002/14651858.cd003261.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for impetigo

Abstract: Analysis 5.1. Comparison 5 Non-bullous impetigo: topical (Top) antibiotic (Ab) vs antifungal (Af), Outcome 1 Cure. Analysis 6.1. Comparison 6 Non-bullous impetigo: topical (Top) antibiotic (Ab) + oral (Or) antibiotic (Ab) vs topical (Top)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 112 publications
0
72
0
12
Order By: Relevance
“…Although SXT is no longer commonly recommended for treatment of respiratory tract infections, it remains one of the most widely used and cheapest antibacterials in the world and is an important option for treatment of SSTI, where S. pyogenes and S. aureus are often copathogens (4,12,24,34). In the era of rising MRSA prevalence, antibacterials that are active against both bacteria are highly valued.…”
Section: Discussionmentioning
confidence: 99%
“…Although SXT is no longer commonly recommended for treatment of respiratory tract infections, it remains one of the most widely used and cheapest antibacterials in the world and is an important option for treatment of SSTI, where S. pyogenes and S. aureus are often copathogens (4,12,24,34). In the era of rising MRSA prevalence, antibacterials that are active against both bacteria are highly valued.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 meta-analysis of 68 treatment trials for impetigo (362) concluded that topical antibiotics, including mupirocin, fusidic acid, and retapamulin, are more effective than placebo and as effective as or more effective than oral antibiotics. There was no difference when mupirocin and fusidic acid were compared head-to-head (362). Penicillin was inferior to erythromycin and cloxacillin.…”
Section: Treatmentmentioning
confidence: 99%
“…Dieses Antibiotikum ist nicht für den systemischen Gebrauch vorgesehen. Diese Empfehlung leitet sich her aus den verfügbaren Evidenzen [11], aber auch aus dem vernünftig-sparsamen Gebrauch wertvoller Ersatzantibiotika [5,6,12]. So hat sich die lokale Anwendung von Mupirocin und Fusidinsäure zwar Die Impetigo contagiosa ist eine primäre, oberflächliche Infektion der Haut (Epidermis) durch beta-hämolysierende Streptokokken oder durch S. aureus.…”
Section: Therapieunclassified
“…Für die kalkulierte orale Therapie bei ausstehender oder fehlender Erregerisolation sind Cefadroxil (1-2 x 1 g/d) oder Cefalexin (3-4 x 1 g/d) -wegen der längeren Halbwertszeit bevorzugen wir Cefadroxil -, Roxithromycin (1 x 0,3 g/d) oder Clarithromycin (2 x 0,5 g/d) zu empfehlen [11,12,16].…”
Section: Therapieunclassified